Exploring the role of cash waqf crowdfunding in economic development: a qualitative study in Northern Nigeria / Jibril Auwal Muhammad and Md. Habibur Rahman - Muhammad, Jibril Auwal; Rahman, Md. Habibur (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
This qualitative study examined the role of cash waqf crowdfunding in economic development in Northern Nigeria. Semi-structured interviews were conducted with six Nigerian scholars and experts, including Shari’ah scholars, social finance officials, and crowdfunding regulators, to explore the challenges, benefits, and impacts of cash waqf crowdfunding. Thematic analysis revealed four primary themes: challenges in implementation, benefits to community development, empowerment of marginalized groups, and promotion of ethical investing. While cash waqf crowdfunding showed promise as a sustainable funding model for community development and poverty alleviation, its practical implementation was constrained by a lack of awareness, trust deficits, and insufficient regulatory frameworks. The f indings underscored the potential of cash waqf crowdfunding to empower marginalized groups, particularly women and youth, and foster community ownership of development projects. This study contributes to the literature on Islamic finance by providing actionable insights for policymakers and practitioners aiming to harness the potential of cash waqf crowdfunding in similar socio-economic contexts.